Exploring the Drivers of Accounting Prudence: Financial Distress, Profitability, and Company Size - Yumniati Agustina; Iwan Setiadi; Afri Rahayuningsih (Indonesia Accounting Research Journal, 2024)
This study investigates the impact of financial distress, profitability, and company size on accounting prudence in financial reporting. Using a regression model, the research explores the individual and collective effects of these variables on the adoption of conservative accounting practices. The results indicate a significant positive correlation between financial distress and accounting prudence, suggesting that companies experiencing financial difficulties tend to adopt more cautious financial reporting practices. Conversely, profitability exhibits a negative relationship with accounting prudence, with more profitable firms less likely to adhere strictly to conservative accounting principles. Company size, however, was found to have no significant impact on accounting prudence. Additionally, the collective influence of financial distress, profitability, and company size was found to significantly shape prudential behavior in financial reporting. The study's findings offer valuable insights for investors and corporate management, suggesting that financial distress levels should be considered when assessing financial reporting practices, while profitability plays a role in determining the level of conservatism in accounting. The study also highlights the need for further research into industry-specific factors that may influence these relationships